PERLINDUNGAN HUKUM TERHADAP PERUBAHAN KLAUSULA BAKU SEWAKTU-WAKTU OLEH JASA LAYANAN PINJAM MEMINJAM UANG BERBASIS TEKNOLOGI INFORMASI - Gilang Putera Moertanto; Rosalinda Elsina Latumahina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The purpose of this study is to find out the regulations for the presence of electronic lending services related to the inclusion of standard clauses by online loan service providers. In the 4.0 era, the rapid progress of information technology gave rise to an innovation that continues to grow, namely the formation of Fintech (Financial Technology) as a combination of information technology and financial services. This technology-based loan service is able to make it easy for people to access loan funds without going through conventional banks. With an agreement between the lender of funds borrower, an agreement will result in a loan agreement which is then referred to as a standard agreement. In this case, the standard agreement does not always benefit the parties who have agreed, but a lot is borne by the consumer. The results of the study show that the regulation of standard clauses related to online lending and borrowing services in the Consumer Protection Act is regulated in Article 18. In addition, in the provisions of the OJK do not explicitly regulate due to the inclusion of a standard clause, so that the rule of law is needed to accommodate these business activities. With the presence of this Consumer Protection Act, it is hoped that it will be able to protect consumer rights so that business actors cannot be arbitrary so as not to cause harm